Detection of RNA modifications - Kaiser, Stefanie; Burhenne, Jürgen; Helm, Mark (RNA biology, 2010)
RNA nucleotide modifications are typically of low abundance and frequently go unnoticed by standard detection methods of molecular biology and cell biology. With a burst of knowledge intruding from such diverse areas as genomics, structural biology, regulation of gene expression and immunology, it becomes increasingly clear that many exciting functions of nucleotide modifications remain to be explored. It follows in turn that the biology of nucleotide modification and editing is a field poised to rapidly gain importance in a variety of fields. The detection and analysis of nucleotide modifications present a clear limitation in this respect. Here, various methods for detection of nucleotide modifications are discussed based on three discriminating principles, namely physicochemical properties, enzymatic turnover, and chemical reactivity. Because the full extent of nucleotide modification across the various RNA species remains ill understood, emphasis is placed on high-throughput techniques with a potential to screen entire transcriptomes.